1990
DOI: 10.1002/bit.260351004
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme loading in a solid support with nonuniform pore size distribution

Abstract: The concept of pore size distribution is incorporated into the Clark model of enzyme immobilization in the present study. This refined model predicted that in the case of small harmonic pore radius with the same surface area and porosity of the support, more enzyme could be loaded in a support with nonuniform pores than that with uniform pores. In comparing the enzyme loading efficiency of the support with two different pore size distributions, the one with Gaussian distribution had the greater amount of enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This gives reasonable predictions of the diffusion coefficient in a dilute solution as long as no major conformational changes occur as a result of charges, for example. Several other predictive equations can be found in the literature 9, 18, 19…”
Section: Theorymentioning
confidence: 98%
See 1 more Smart Citation
“…This gives reasonable predictions of the diffusion coefficient in a dilute solution as long as no major conformational changes occur as a result of charges, for example. Several other predictive equations can be found in the literature 9, 18, 19…”
Section: Theorymentioning
confidence: 98%
“…Loh et al17 studied pore size distributions using mercury intrusion experiments and found similar results for other porous media. Chiang et al18 compared different pore size distributions for enzyme loading. Li et al19 calculated average pore diameters for agarose and alginate gels, giving an average pore diameter in good agreement with the data of Medin.…”
Section: Introductionmentioning
confidence: 99%
“…Loh et al 17 studied pore size distributions using mercury intrusion experiments and found similar results for other porous media. Chiang et al 18 compared different pore size distributions for enzyme loading. Li et al 19 calculated average pore diameters for agarose and alginate gels, giving an average pore diameter in good agreement with the data of Medin.…”
Section: Introductionmentioning
confidence: 99%